2017
DOI: 10.1073/pnas.1702502114
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation onset caused by acceleration

Abstract: Striking the top of a liquid-filled bottle can shatter the bottom. An intuitive interpretation of this event might label an impulsive force as the culprit in this fracturing phenomenon. However, highspeed photography reveals the formation and collapse of tiny bubbles near the bottom before fracture. This observation indicates that the damaging phenomenon of cavitation is at fault. Cavitation is well known for causing damage in various applications including pipes and ship propellers, making accurate prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…2017, 2018; Pan et al. 2017) and fabrication of drug delivery systems (Tagawa et al. 2013; Battula, Menezes & Hosseini 2016; Moradiafrapoli & Marston 2017; Kiyama et al.…”
Section: Introductionmentioning
confidence: 99%
“…2017, 2018; Pan et al. 2017) and fabrication of drug delivery systems (Tagawa et al. 2013; Battula, Menezes & Hosseini 2016; Moradiafrapoli & Marston 2017; Kiyama et al.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that cavitation induced by an impulsive system can be better defined by acceleration rather than speed 1 . Here we calculated the cavitation number as Ca = (p r − p v )/(ρLa max ) 1 , where p r is the atmospheric pressure, p v is the vapor pressure, ρ is the water density, and L is the distance between the start and end positions of water level in the tube, respectively. We found that knifefish suction feeding generates Ca of 0.65 (± 0.20 SD, N = 4), which sufficiently meets the criteria to generate cavitation (Ca < 1).…”
Section: Resultsmentioning
confidence: 99%
“…Cavitation bubbles in a liquid are induced by intense and sudden changes of local pressure 1 . These collapsing bubbles can produce intense compressional waves and extremely high temperatures, as well as serious damage on structures.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, p ∝ ah (see Eq. S3 in the supplementary document) is often used to estimate p where a and h are acceleration and a coordinate of the sample in the impact direction because directly measuring p in pure water 24 and soft gels 15 during impact is still experimentally challenging. In this regard, we theoretically consider below how p , λ and h are linked to each other and show p ∝ ah is not a good estimation for the acceleration-induced pressure gradient for soft gels.…”
Section: Resultsmentioning
confidence: 99%
“…One notable advance is in the characterization of cavitation properties for soft materials under an impulsive force 15 , 24 where the critical acceleration that corresponds to the onset of the bubble formation and bursts is quantitatively measured. While the acceleration-induced pressure is the primary driving force for this rapid material deformation associated with bubble dynamics in pure water and gelatin samples, the spatio-temporal dynamics in soft material samples during mechanical impact remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%